Attitude towards compulsory rural health services among interns of RajaRajeswari Medical College and Hospital, Bengaluru - S. C., Ranganatha; M. N., Damayanthi; Jailkhani, Sheetu (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, majority of Doctors are working in urban than rural areas. Health situation report suggests that medical students should be provided with a rural clinical placement to make them familiar with the rural workplace. Hence the present study was conducted with the aim of assessing the attitude of the interns of RajaRajeswari Medical College and Hospital (RRMCH), Bengaluru, towards compulsory Rural Health Services. Methods: A cross sectional study was conducted at RRMCH, Bengaluru for a period of two months. All the interns willing to participate and present on the day of study were included. Consent was taken and the information was collected by using a self administered semi-structured questionnaire. The participants were asked to respond on a five point Likert scales, ranging from strongly agree to strongly disagree. The data was analyzed using SPSS version 21.0 and Pearson’s chi-square test was applied. Results: Out of 100 interns, majority (56%) was females, 85% were Hindu by religion and 68% were from urban locality. Out of 100 interns, only 14% showed positive attitude towards compulsory rural health services. The reasons for positive attitude were that it provides a good exposure of general practice and an opportunity for independent working. Conclusions: In the present study, only 14% interns showed positive attitude towards rural health services. Perceived factors such as Isolation from family and Inadequate Hospital infrastructure emerged as barrier for the interns to opt for rural services.